PA.45 Hand Hygiene in an Obstetric Out-Patient Clinic: is it really possible to follow recommendations?. (9th June 2014) - Kiafar, S; Brophy, C; Dunne, AM; Mahony, R; Higgins, M; Knowles, S
Abstract : Background: Substantial evidence has proven that careful hand hygiene will reduce healthcare-associated infection (HCAI). However, lack of systemic evaluation of the risk of HCAI in an out-patient setting, as well as practical barriers to implement the world health organisation (W.H.O) five-moments of hand hygiene in a busy maternity clinic, challenges implementation. The aim os this study was to determine the number of hand hygiene actions that staff in a maternity out-patient clinic should take and the time required, if recommendations are implemented in full. Method: Direct observational audit during a routine working day. All indications for the 5-moments of hand hygiene were observed. Results: Seven staff including two receptionists, three midwives, one obstetrician and one healthcare-assistant participated in the audit. One hundred and forty seven patients attended the clinic, which is normal attendance. Collectively, 1228 hand hygiene opportunities were indicated for staff, varying from 14 to 353 per person. This equates to 13 h of hand hygiene and respective timings varied from 9 minutes to 3 h3 hours 36 min per staff person. Contact with the patients surroundings accounted for 61% (751) of hand hygiene opportunities. Conclusion: Hand hygiene is acknowledged as the most important means of preventing transmission of infection in any healthcare setting. However, strictly advocating all 5-moments of hand hygiene in a low risk maternity out-patient-clinic is challenging for staff and is considered impractical, especially in relation to contact with the patient surroundings in the absence of a specific infection risk.